Turning to train in the moment of high fuel prices: could it be a new option for urban commuters in Ghana? - Michael Tuffour; Daniella D. Sedegah; Efua E. Mantey; Bernice O. Owusu (Cogent Social Sciences)
Out of the various forms of commercial transport among the working class in Ghana’s capital city, Accra, the least patronized is train. This is due to its perceived unavailability, unreliability and unattractiveness. The excessive increase of transport prices in Ghana arising from an upsurge in the global fuel prices have tremendously increased railway patronage, making it the preferred means of transport among the city’s working class who use public transport and have access to it. This study assessed the positive factors that underscore the use of train, the underlying negative factors and the possibility of sticking to train by urban dwellers. Within the qualitative methodology approach of a grounded theory, a total of thirty-five in-depth interviews were conducted and analysed. The results indicate train is an economic life saver and also serves as an excellent alternative to the other competing transport services even though the coaches overcrowded, the technology used is outmoded and travelling with it makes commuters uncomfortable. The moment creates an opportunity for urban commuters to turn to train as a new norm for urban transport during high inflationary periods. It also presents an opportunity for urban authorities, government and other stakeholders to reconsider expanding the urban rail system to make it a viable transport alternative.